Pregnancy Outcomes After Abdominal Radical Trachelectomy for Early-Stage Cervical Cancer: A 13-Year Experience in a Single Tertiary-Care Center. Issue 1 (1st January 2016) - Kasuga, Yoshifumi; Nishio, Hiroshi; Miyakoshi, Kei; Sato, Suguru; Sugiyama, Juri; Matsumoto, Tadashi; Tanaka, Kyoko; Ochiai, Daigo; Minegishi, Kazuhiro; Hamatani, Toshio; Iwata, Takashi; Morisada, Tohru; et al.
Abstract : Objective: To investigate pregnancy outcomes in women after abdominal radical trachelectomy (RT) for early-stage cervical cancer. Methods: The patients' background, fertility, and pregnancy outcomes were reviewed in a total of 61 pregnancies in 48 of 172 women who underwent abdominal RT at Keio University Hospital between September 2002 and December 2013. Results: There were 5 women with stage IA1, 2 with stage IA2, and 41 with stage IB1. Histological types were as follows: squamous cell carcinoma (n = 36), adenocarcinoma (n = 10), and adenosquamous cell carcinoma (n = 2). The pregnancy rate of women attempting to conceive after abdominal RT was 44% (48/109). The mean ± SD duration from abdominal RT to conception was 3.1 ± 1.9 years. Of 61 pregnancies, 42 pregnancies were achieved by fertility treatment (in vitro fertilization-embryo transfer, 39; intrauterine insemination, 3). After excluding one pregnancy without detailed clinical information, there were 42 live births (5 in 22–27 weeks, 11 in 28–33weeks, 20 in 34–36 weeks, and 6 in 37–38 weeks), 13 miscarriages, and 5 ongoing pregnancies. While there were 10 first trimester miscarriages, 3 pregnancies ended in the second trimester owing to chorioamnionitis. The mean gestational age at birth was 33 weeks of pregnancy. Thirty-seven neonates were appropriate-for-date, and one was small-for-date. Six pregnancies exhibited massive bleeding from the residual cervix in the late pregnancy. Preterm birth less than 34 weeks of pregnancy was related to premature rupture of the membrane ( P < 0.05). Chorioamnionitis was evident in 9 of 11 pregnancies with preterm premature rupture of the membrane followed by birth at less than 34 weeks of pregnancy. No parturients exhibited lochiometra and endometritis postpartum. Conclusions: Abdominal RT provided favorable pregnancy outcomes, and fertility treatment could be advantageous to conception. Massive bleeding from the residual cervix as well as ascending infection might be characteristic features during pregnancy after abdominal RT.